Be my ghost - Perry, Carol J. (Perry, Carol J. Haunted Haven mystery., 2021)
"Maureen Doherty and her golden retriever Finn have taken possession of a charming old inn--only to discover that it's already possessed by tenants whose lease on life already ran out ..."--